2020
DOI: 10.1002/trc2.12034
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow and cognitive functioning in patients with disorders along the heart–brain axis

Abstract: Introduction We examined the role of hemodynamic dysfunction in cognition by relating cerebral blood flow (CBF), measured with arterial spin labeling (ASL), to cognitive functioning, in patients with heart failure (HF), carotid occlusive disease (COD), and patients with cognitive complaints and vascular brain injury on magnetic resonance imaging (MRI; ie, possible vascular cognitive impairment [VCI]). Methods We included 439 participants (124 HF; 75 COD; 127 possible VC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 43 publications
0
17
1
Order By: Relevance
“…The changes noted in the CBF volume were examined in three studies ( 21 , 23 , 24 ), which elucidated that the combination of CBF decline with AF, depression, or BMI may result in higher number of adverse effects on attention, executive function, memory, and other cognitive areas of HF patients. However, one study ( 18 ) indicated that the CBF value was lower in the HF group, whereas no significant correlation was noted between CBF and CI compared with the control group.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The changes noted in the CBF volume were examined in three studies ( 21 , 23 , 24 ), which elucidated that the combination of CBF decline with AF, depression, or BMI may result in higher number of adverse effects on attention, executive function, memory, and other cognitive areas of HF patients. However, one study ( 18 ) indicated that the CBF value was lower in the HF group, whereas no significant correlation was noted between CBF and CI compared with the control group.…”
Section: Resultsmentioning
confidence: 97%
“…A total of 403 articles were excluded of the 469 remaining articles, following investigation of the full text. Finally, 66 studies ( 18 83 ) were included in the analysis, involving a total of 33,579 patients. The flow chart ( Figure 1 ) indicates the search process and study selection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several factors, including large artery stenosis and occlusion due to atherosclerotic disease, hypotension, or anemia, may underlie the development of this subtype of stroke [ 38 , 39 , 40 ]. The decrease in cerebral blood flow may be further compromised due to the reduced cardiac output in patients with HF in the presence of large artery stenosis [ 41 , 42 ]. The cerebral hypoperfusion leads to a decrease in blood flow to the areas of brain supplied by deep arteries lacking collateral flow, which makes them vulnerable to ischemic damage [ 21 ], vascular dementia [ 43 , 44 ], silent or subclinical stroke, and cognitive impairment [ 14 , 45 , 46 ].…”
Section: Etiology Of Stroke and Risk Factors In Heart Failurementioning
confidence: 99%
“… 57 , 58 However, a recent study showed no relation between cerebral blood flow, measured with arterial spin labelling MRI, and cognitive functioning in patients with HF and vascular brain injury. 59 In two studies comparing patients with HF to controls, medial temporal lobe atrophy (MTA) was related to cognitive functioning in patients with HF. 47 , 60 MTA is an early feature of Alzheimer’s disease (AD) and is associated with an increased risk of progression to dementia.…”
Section: Heart and Brainmentioning
confidence: 99%